2008
DOI: 10.1073/pnas.0710518105
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-mediated reversible dissociation of a stromal multiprotein complex in response to changes in light availability

Abstract: A Calvin cycle multiprotein complex including phosphoribulokinase (PRK), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and a small protein, CP12, has previously been identified. In this article, we have studied this complex in leaves and have shown that dissociation and reassociation of the PRK/GAPDH/CP12 complex occurs in a time frame of minutes, allowing for rapid regulation of enzyme activity. Furthermore, we have shown that the extent of formation and dissociation of the PRK/GAPDH/CP12 complex correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
133
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 36 publications
8
133
1
Order By: Relevance
“…Support for the importance of CP12 in mediating the formation of this complex has come from in vitro experiments utilizing recombinant expressed proteins or partially purified components. These data have demonstrated that complex formation is dependent upon the presence of oxidized CP12 (Scheibe et al, 2002;Marri et al, 2005), and recent evidence suggests that this is mediated by changes in the redox state of thioredoxin f (Howard et al, 2008;Marri et al, 2009).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Support for the importance of CP12 in mediating the formation of this complex has come from in vitro experiments utilizing recombinant expressed proteins or partially purified components. These data have demonstrated that complex formation is dependent upon the presence of oxidized CP12 (Scheibe et al, 2002;Marri et al, 2005), and recent evidence suggests that this is mediated by changes in the redox state of thioredoxin f (Howard et al, 2008;Marri et al, 2009).…”
mentioning
confidence: 76%
“…This complex has been shown to be present in several higher plant species (Wedel et al, 1997;Wedel and Soll, 1998;Scheibe et al, 2002;Howard et al, 2011), in algal species (Avilan et al, 1997;Boggetto et al, 2007;Oesterhelt et al, 2007), and in a cyanobacterium (Tamoi et al, 2005). Furthermore, dissociation and aggregation of this complex in pea (Pisum sativum) leaves are rapid and respond to light quantity (Howard et al, 2008). Support for the importance of CP12 in mediating the formation of this complex has come from in vitro experiments utilizing recombinant expressed proteins or partially purified components.…”
mentioning
confidence: 99%
“…This is interesting because, as in higher plants, the formation and breakdown of the PRK-GAPDH complex is mediated by the redox state of CP12, which in turn is mediated by thioredoxin (Howard et al, 2008;Marri et al, 2009).…”
Section: The Role Of the Cp12-associated Cbs Domainmentioning
confidence: 99%
“…The formation of the GAPDH-PRK-CP12 complex inhibits GAPDH and PRK activity leading to down-regulation of the Calvin cycle; this has been demonstrated in plants, Chlamydomonas reinhardtii, and cyanobacteria (Wedel et al, 1997;Graciet et al, 2003a;Marri et al, 2005b;Tamoi et al, 2005). The GAPDH-PRK-CP12 complex dissociates under reducing conditions mediated by thioredoxin, thereby restoring GAPDH and PRK activity (Lebreton et al, 2003;Marri et al, 2005bMarri et al, , 2009Howard et al, 2008). Erales et al (2008a) showed that CP12 binds aldolase, another Calvin cycle enzyme, implying the involvement of CP12 in additional Calvin cycle regulation.…”
mentioning
confidence: 92%
See 1 more Smart Citation